First insights in bacteria diversity in headwaters emerging from Alpine rock glaciers - Tolotti, M.; Albanese, D.; Cerasino, L.; Donati, C.; Pindo M.; Rogora M.; Seppi R. (country:FR, 2018)
Global warming exerts particularly pronounced effects on the European Alps. As the thawing rates of mountain permafrost ice is lower than for glacier ice, a shift from glacial/periglacial to paraglacial/periglacial dynamics is predicted for Alpine landscapes during the 21st century in relation to deglaciation. Poor knowledge exists on chemical and biological features of waters emerging from Alpine rock glaciers. A set of glacial- or permafrost-fed headwaters was investigated in the Eastern Italian Alps, aiming at exploring bacterial community composition and diversity in epilithic biofilm and sediments. Bacterial assemblages show significant differences according to water and sample type, and to catchment geology. Rock glacier-fed waters show enhanced conductivity and trace element concentrations, and their highly diverse bacterial assemblages significantly differ only from those of glacial streams. Further research will better outline the role of environmental features in modulating bacterial diversity of Alpine headwaters affected by progressing deglaciation.